Inclusion of Bioethics in Curricula of Rawalpindi medical university: Perception of Teachers and Students about Teaching and Learning Process A cross sectional study - Syed Naqvi, Syed Tabeer; Saba Sajid, Laweeza Fatima, Ajwa Arsalan, Dr. Imrana, Dr. Sana Bilal (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Background: The change in trend of medicine has made it important that bioethics should be included curricula. The paternalistic approach of doctors can be changed via teaching bioethics. Many Countries are recognizing bioethics as an important part of their curricula, which has already been included in the curricula of Rawalpindi Medical University, Pakistan. Objectives: The objectives of this study are to assess the perception of students about inclusion of bioethics and hurdles encountered by teachers as educators and to identify the effective mode of teaching. Material and Methods: A Cross-Sectional Study was conducted in Rawalpindi Medical University Pakistan in a time period of 6 months.400 MBBS students of all academic years, while 23 faculty members from clinical and basic sciences took part in study. Perception about bioethics was assessed using a self-structured questionnaire, comprised of two parts; a student questionnaire and a teachers’ section, containing both close and open-ended questions The student questionnaire was validated and its Cronbach’s alpha value is 0.677. Descriptive Analysis was performed using SPSS version 23. Results: The perception of students about inclusion of bioethics show that 56.5% (N=226) of participants agree that teaching bioethics will help them develop skills to solve ethical dilemmas. 23.5% (N=94) of participants strongly agree that formal teaching of bioethics should be emphasized and strengthened. 54.3% (N=217) of participants agree that assessment of bioethics should be made necessary. On the other hand, Teacher analyses showed that 91.3% (N=21) of the teachers agree upon the necessity of assessment of Bioethics. The only specific challenge for teachers was lack of special training.45.3% (N=181) of students think Role-play as the preferred method of teaching Bioethics. Conclusion: It is concluded in the study that bioethics should be included in the curricula and students and teachers alike consider it important to assess. With the modernization and setting of different trends in the medical practice, the inclusion of bioethics is the need of the time. The different perception of students and the effective method of teaching of bioethics have been discussed. Keywords: Bioethics, Challenges, and Perception